Recent advances in the development of a chemically synthesised anti-malarial vaccine (2015)
Introduction: Obtaining an effective antimalarial vaccine has represented one of the biggest public health challenges over the last 50 years. Despite efforts by many laboratories around the world using whole-organism, recombinant proteins and genome-based approaches, the results have been disappointing. One of the main problems when designing an antimalarial vaccine is the poor immunogenicity induced by the functionally relevant and conserved protein regions of the parasite. Areas covered: This review focuses on the logical and rational methodology followed to identify Plasmodium falciparum conserved functional regions with the ability to bind to target cells conserved high activity binding peptides (cHABPs) and the physicochemical and immunological characteristics that should be taken into account for modifying them into highly immunogenic and protection-inducing peptides (mHABPs) into highly immunogenic and protection-inducing in Aotus monkeys. Expert opinion: The functional approach taken to develop a fully protective, minimal subunit-based, multiantigenic, multistage and synthetic peptide-based antimalarial vaccine has shown promising results. The clear relationship observed between mHABPs structure and their immunological properties highlights the challenges and opportunities arising from this methodology, as well as the universal principles and rules derived therefrom. © 2015 Taylor and Francis.